2022
DOI: 10.1152/japplphysiol.00835.2021
|View full text |Cite
|
Sign up to set email alerts
|

A leak-free head-out plethysmography system to accurately assess lung function in mice

Abstract: Mice are a valuable model for elegant studies of complex, systems-dependent diseases, including pulmonary diseases. Current tools to assess lung function in mice are either terminal or lack accuracy. We set out to develop a low-cost, accurate, head-out variable-pressure plethysmography system to allow for repeated, non-terminal measurements of lung function in mice. Current head-out plethysmography systems are limited by air leaks that prevent accurate measures of volume and flow. We designed an inflatable cuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Tidal breathing comparison between lean and diet-induced obese male mice for variables collected using head-out plethysmography. The authors have reported a subset of group (n=9 lean mice tidal breathing & response to methacholine) previously(14). For all graphs lean n=23 obese n=29; results presented as mean + SEM.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tidal breathing comparison between lean and diet-induced obese male mice for variables collected using head-out plethysmography. The authors have reported a subset of group (n=9 lean mice tidal breathing & response to methacholine) previously(14). For all graphs lean n=23 obese n=29; results presented as mean + SEM.…”
Section: Resultsmentioning
confidence: 99%
“…High fat diet (HFD: Tekland WI TD 06414) was provided at 12 weeks of age for 9 weeks. At 21 weeks of age, we assessed lung function in chow fed lean (24.4 + 0.7 grams) and diet-induced obese mice (40.8 + 1.2 grams) with head-out plethysmography and subsequently measured lung mechanics using forced oscillation technique in a subset of mice (14).…”
Section: Micementioning
confidence: 99%
See 3 more Smart Citations